(untitled) (Journal of Dhaka Medical College, 2017)
Introduction: Ludwigs angina is a rapidly progressive, potentially fulminant cellulitis involving the sub-lingual, submental and sub-mandibular spaces. It typically originates from an infected or recently extracted tooth, most commonly the lower second and third molars. Besides, poor nutritional status, lack of proper medical supports are still major predisposing factors in developing Ludwigs angina in countries like Bangladesh. Aim: Our study aimed to observe the role of odontogenic infection in development of Ludwigs Angina. Method: We carried out a cross sectional study among 26 patients with Ludwigs angina admitted in the department of ENT and Head-neck surgery in SSMC &Mitford Hospital from January-December-2014. Results: In this study we found that males are predominantly affected than females (21 males and 5 females, ratio-4.2:1) with odontogenic infection (18, 69%) as source. We found historyof recent tooth extraction in 6 cases (23%) & organism was isolated from pus culture,Klebsiella in 10 cases (19.2%) out of 26 cases. We elicited underlying systemic disease mainly is Diabetes Mellitus in 9 cases (35%) that predisposes to Ludwigs angina. Conclusion: Our study suggests that prompt and thorough clinical evaluation and definitivecare will considerably improve patient condition and reduce morbidity and mortality. J Dhaka Medical College, Vol. 26, No.1, April, 2017, Page 3-7